Peran Siswa Sekolah Dasar dalam Perubahan Perilaku Pembuangan Sampah Organik dan Pemanfaatan Pembuangan Akhir - Daniah daniah; Ekamaulana Nurzanah; Carwadi Carwadi (UIMA Press, 2019)
Abstract Introduction: Waste can cause health and safety of the environment, if the waste is not managed properly. Objective: The purpose of this research is elementary students can find out the difference between organic and non-organic waste, elementary school students also so they can make changes in dumping rubbish to the final dumpsite. Design: This type of research is quantitative, using Quasi Experiment. Measurements were made 2 times Pre and post. Performed at SDN Sukaluyu Kec.Teluk Jambe District. Karawang. The population in this study Class 6 students were 51 people. Result: Results of the analysis The effect of the intervention on knowledge increased by 8.3 after the intervention. Statistical test results show a P value of 0,000 which means that the intervention has a significant effect on increasing knowledge. attitude increased by 5.1 after the intervention. Statistical test results showed a P value of 0,000, which means that the intervention has a significant effect on increasing attitude scores. Conclusion: The results of the study concluded the average influence of the increase in knowledge after the intervention, and the existence of behavior change.